ChemInform Abstract: Construction of Multiple, Contiguous Quaternary Stereocenters in Acyclic Molecules by Lithiation‐Borylation. Issue 23 (June 2015) - Watson, Charlotte G.; Balanta, Angelica; Elford, Tim G.; Essafi, Stephanie; Harvey, Jeremy N.; Aggarwal, Varinder K.
Abstract Using the lithiation of chiral carbamates followed by borylation, carbon chains bearing multiple contiguous quaternary stereogenic centers can be constructed with high enantio‐ and diastereoselectivity.